Meningitis following cerebrospinal fluid-cutaneous fistula secondary to combined spinal-epidural anaesthesia for elective caesarean delivery. (February 2022) - Gordon, C.; Fry, C.; Salman, M.; Desai, N.
Highlights: Postpartum fluid leak after a neuraxial procedure poses a diagnostic conundrum. Cerebrospinal fluid-cutaneous fistula is rare but has potential serious consequences. A case of meningitis possibly secondary to cerebrospinal fluid-cutaneous fistula. Abstract: Cerebrospinal fluid-cutaneous fistula is a rare complication associated with neuraxial procedures. Here, we describe a case of fistula formation related to combined spinal-epidural anaesthesia for elective caesarean delivery, where the epidural catheter was removed only two hours later. The clear fluid leaking persistently from the site of the skin puncture associated with the epidural insertion site was confirmed to be cerebrospinal fluid with an increased beta-trace protein, and the fistula was closed with skin sutures. Subsequently, the patient presented with neurological signs and symptoms consistent with meningitis and was treated empirically with intravenous antibiotics. Cerebrospinal fluid-cutaneous fistula formation with secondary meningitis is an exceptionally rare event in obstetric anaesthesia.